2008
DOI: 10.17305/bjbms.2006.3128
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy in Treatment of Cervical HrHPV Infection by Combination of Beta Interferon, and Herbal Therapy in Woman with Different Cervical Lesions

Abstract: Cervical dysplasia, a premalignant lesion that can progress to cervical cancer, is caused primarily by a sexually transmitted infection with an oncogenic strain of the human papillomavirus (HPV). The HPV infections are treated through destroying the clinical lesions: laser, cryotherapy, podophyllin... The hope is that by causing local tissue inflammation that the body will be stimulated to mount an antibody response and thereby prevent recurrence. In contrast to other prevention approaches, vaccines can reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…juice, Echinacea purpurea (L.) Moench and Calendula officinalis L.). After 3 months, HPV infection was still present in more than 90% of the subjects in the control group, while had disappeared in 71.42% of the patients in the treatment group and in 100% after 6 months 74 . In this study, however, propolis was formulated with other natural products and associated with interferon, making it impossible to dissect its individual contribution to therapeutic success.…”
Section: Antiviral Activitymentioning
confidence: 79%
“…juice, Echinacea purpurea (L.) Moench and Calendula officinalis L.). After 3 months, HPV infection was still present in more than 90% of the subjects in the control group, while had disappeared in 71.42% of the patients in the treatment group and in 100% after 6 months 74 . In this study, however, propolis was formulated with other natural products and associated with interferon, making it impossible to dissect its individual contribution to therapeutic success.…”
Section: Antiviral Activitymentioning
confidence: 79%
“…This difference could be due to the type of extract and/or the species of plant or some unknown factors. In other studies, stimulation of immune system against some viral complications due to Aloe extract were established (Gauntt et al, 2000;Iljazovic, 2006). Therefore, an in vivo study on the antiviral activity or another aspect of medical applications of the A. vera of Bushehr is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that propolis-containing local therapy can eradicate HPV infections within six months. In a randomized trial, HPV infections were present after three months of treatment in 28% of patients treated with propolis compared to 90% in the control group [55].Similarly, another study described an improvement in cytological PAP smears (Papanicolaou test) of…”
Section: Uses Of Propolismentioning
confidence: 94%